Brooke at the bar: inside our legal system - Wunnicke, Brooke, author; Wunnicke, Diane B., compiler; University Press of Colorado, publisher (Colorado State University. Libraries, 2023)
Brooke Wunnicke was the first woman to be a trial and appellate attorney in Wyoming, laying the foundation for future generations of female attorneys. Brooke at the Bar is a lively, personal and humorous autobiography including reflections on the legal system and what it means in the United States.--Provided by publisher.
Keywords: Women lawyers -- Colorado -- Denver -- Biography; Women lawyers -- Wyoming -- Cheyenne -- Biography; Lawyers -- Colorado -- Denver -- Biography; Lawyers -- Wyoming -- Cheyenne -- Biography; Wunnicke, Brooke